خروج الدابّة دراسة حديثية عقدية في ضوء القرآن والسنة - Burgan, I. M.; Rasheed, M. A. (Universiti Sains Islam Malaysia, 2024)
This paper discusses the issues of "the beast of earth" from hadith and creedal points of view. It explains the literal and technical meanings of this beast, the proofs on its emergence, its timing, its order among the other signs, its features and the effect it will have on peole. This research is based on the Qur'anic verses and Prophetic hadiths on the subject for an authoritative view about the issue in question, in addition to analyzing all the relevent texts. The study has come to the conclusion that the emergence of the beast is one of the major signs of the Hour. In fact, it will appear at noon time. Nonetheless, hadiths on its effect on people are mostly baseless and unreliable. As such, it is important to rely solely on the Quran on this matter.